2012
DOI: 10.1101/gr.140988.112
|View full text |Cite
|
Sign up to set email alerts
|

Genome and transcriptome sequencing of lung cancers reveal diverse mutational and splicing events

Abstract: Lung cancer is a highly heterogeneous disease in terms of both underlying genetic lesions and response to therapeutic treatments. We performed deep whole-genome sequencing and transcriptome sequencing on 19 lung cancer cell lines and three lung tumor/normal pairs. Overall, our data show that cell line models exhibit similar mutation spectra to human tumor samples. Smoker and never-smoker cancer samples exhibit distinguishable patterns of mutations. A number of epigenetic regulators, including KDM6A, ASH1L, SMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
137
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(142 citation statements)
references
References 67 publications
3
137
0
2
Order By: Relevance
“…However, tumor cells with up-regulated Rac1b may partially survive this situation and thus greatly aggravate the process of the diseases. Our results support previous reports showing that up-regulated Rac1b can contribute to the tumor progression and metastasis [6,[16][17][18] .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, tumor cells with up-regulated Rac1b may partially survive this situation and thus greatly aggravate the process of the diseases. Our results support previous reports showing that up-regulated Rac1b can contribute to the tumor progression and metastasis [6,[16][17][18] .…”
Section: Discussionsupporting
confidence: 93%
“…Apart from its constitutive activity, significantly upregulated Rac1b expression has been reported to be deeply involved in tumorigenesis and the metastasis of colorectal, breast, lung, and thyroid cancers [6,[16][17][18] . Transient overexpression of Rac1b in cultured cells was able to promote cell proliferation [19] .…”
Section: Introductionmentioning
confidence: 99%
“…One particular example is the tumor-related splicing variant Rac1b, an isoform of the signaling GTPase Rac1 (Matos et al 2003), in which a usually skipped exon 3b is retained. The resulting protein isoform Rac1b is overexpressed in a specific subtype of colorectal tumors and required to sustain tumor cell survival (Jordan et al 1999;) but was also reported in breast, lung, and thyroid tumors (Schnelzer et al 2000;Radisky et al 2005;Liu et al 2012;Stallings-Mann et al 2012;Silva et al 2013;Zhou et al 2013). Interestingly, Rac1b was found to be predominantly in the signaling-competent GTP-bound conformation (Schnelzer et al 2000;Matos et al 2003;Fiegen et al 2004;Radisky et al 2005), so that small changes in its expression level yield significant cellular responses.…”
Section: Introductionmentioning
confidence: 98%
“…Although the role of the human ortholog of Pat1 (Pat1b) in kinetochore function has not been defined, nuclear localization of Pat1b has been observed in humans (Marnef et al 2012). Furthermore, mutations and misregulation of Pat1b have been observed in several human cancers (Araujo et al 2012;Liu et al 2012;Dulak et al 2013). Hence, future studies aimed at understanding the role of the human homolog of Pat1 in the structure and function of the kinetochore may help us identify potential therapeutic targets for cancer therapy.…”
Section: Discussionmentioning
confidence: 99%